Improving the uptake and comprehensiveness of bedside cognitive testing amongst liaison psychiatrists over an eight-month period. - McCormack, Ruaidhri (BMJ Qual Improv Rep, 2016)
The aim of this quality improvement (QI) project was to improve the uptake and comprehensiveness of bedside cognitive testing amongst liaison psychiatrists over an eight month period. The baseline measurement involved an audit of the practice of the neuropsychiatry liaison team over six months at the 840 bed St Thomas's Hospital in London, UK. Of 35 referrals, 21 patients were able, and suitable, for cognitive testing based on the referral data and clinical interview. Fourteen (66.6%) of these patients had an Addenbrooke's Cognitive Examination (ACE), while 5 (23.8%) had frontal testing. The frontal tests performed were variable and inconsistent. Two Plan-Do-Study-Act (PDSA) cycles were then conducted. Clear guidance was issued to the team on the use of the ACE or Montreal Cognitive Assessment (MoCA) in suitable patients, and how these can be supplemented by frontal testing. Given the inconsistency in the types and combination of frontal tests being conducted at baseline, a frontal lobe test sheet containing established tests was developed and implemented. In PDSA cycle 1, 100% (n=10) of able and suitable referrals had an ACE or MoCA while 100% had frontal testing (80% of these using the dedicated test sheet). In PDSA cycle 2, improvements were broadly maintained with 85.7% (n=6) of referrals having an ACE/MoCA and 85.7% having frontal testing (83.3% of these using the dedicated frontal test sheet). In conclusion, our team improved the uptake and comprehensiveness of bedside cognitive testing by changing existing practice with clear protocols regarding the use of the ACE/MoCA and the implementation of a frontal test sheet.